Development of Virtual Learning Environment Based on Constructivism to Enhance Computational Thinking Skills in Grade 10 Students Taking Computing Science Course 1 - Pooyang, Ismaal; Kaosaiyaporn, Ophat; Lateh, Afifi (Journal of Information and Learning [JIL], 2023)
The purposes of this research were 1) to develop a virtual learning environment based on constructivism to enhance computational thinking skills in grade 10 students taking Computing Science course 1, 2) to compare the computational thinking skills of learners before and after exposure to the virtual learning environment, and 3) to compare reflections of learners before and after exposure to the virtual learning environment. The research employed a Research and Development (R&D) design consisting of two phases, as well as a one-group posttest-only design. The target group consisted of 25 grade 10 students who were ready for a constructivist-based virtual learning environment. The research instruments included a virtual learning environment based on constructivism in Computing Science course 1, a computational thinking ability test, and a reflection assessment form. The statistics used for the analysis were mean, standard deviation, and t-test. The findings were as follows. First of all the quality of the constructivist-based virtual learning environment was rated at an appropriate level (M = 4.63, SD = 0.55). Second, the computational thinking abilities of learners after exposure to the proposed virtual learning environment was at a good level (M = 78.55) and represented 78.55 percent at a significant level of .01. Finally, the reflection of learners after exposure to the proposed virtual learning environment was at a good level (M = 63.73) and represented 84.97 percent at a significant level of .01.